Indonesia : 2007 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Indonesia. (IMF Staff Country Reports; Country Report, 2007)
This 2007 Article IV Consultation highlights that Indonesia's economic performance has been strong since the last Article IV Consultation. Supported by sound policies and a favorable external environment, output has grown strongly, inflation has stabilized, and international reserves have risen to an all-time high. The government, banking, and corporate sectors continued to reduce balance sheet vulnerabilities. Indonesia's financial markets have rallied in line with global trends and perceptions that risks have been reduced. The government continues to implement its comprehensive reform agenda to boost growth over the medium term.